Nuclear quantum tunnelling and carrier delocalization effects to bridge the gap between hopping and bandlike behaviors in organic semiconductors. Issue 1 (21st October 2015) - Jiang, Yuqian; Zhong, Xinxin; Shi, Wen; Peng, Qian; Geng, Hua; Zhao, Yi; Shuai, Zhigang
Abstract : Our research investigated the significant role of nuclear tunnelling and carrier delocalization effects in the charge transport process of organic semiconductors. Abstract : The experimental carrier mobility value of organic semiconductors has been increasing rapidly in recent years to well exceed the theoretical limit based on the hopping model calculated using the semi-classical Marcus theory, calling for better understanding and evaluation of carrier mobility. On the other hand, bandlike transport behavior has been observed for some ultra-pure and closely-packed organic single crystals. In this work, we identify the roles of quantum nuclear tunnelling and the charge delocalization effects, leading to a comprehensive computational approach to assess the carrier mobility of organic semiconductors. We present the first-principles evaluated mobility results for some representative organic transport materials at four levels ranging from semiclassical hopping to quantum nuclear enabled hopping and to quantum wavepacket diffusion, and eventually to complete bandlike descriptions. We provide a comprehensive tool to assess the carrier mobility in organic semiconductors based on such improved understanding.